Supplementary material for "RcgA and RcgR, two novel proteins involved in conjugative transfer of rhizobial plasmids" - Castellani, Lucas Gabriel (2022)
Rhizobia are gram-negative bacteria able to establish a nitrogen-fixing symbiotic interaction with leguminous plants. Rhizobia usually harbor several plasmids in their genome which can be transferred to other organisms by conjugation. Two main mechanisms of regulation of rhizobial plasmid transfer have been described: Quorum sensing (QS) and rctA/rctB system. Nevertheless, new genes and molecules that modulate conjugative transfer have been recently described, demonstrating that new actors can tightly regulate the process. In this work, by means of bioinformatics tools and molecular biology approaches, two hypothetical genes were identified as playing key roles in conjugative transfer. These genes are located between conjugative genes of plasmid pRfaLPU83a from Rhizobium favelukesii LPU83, a plasmid that shows a conjugative transfer behavior depending on the genomic background. One of the two mentioned genes, rcgA, is essential for conjugation, while the other, rcgR, acts as an inhibitor of the process. In addition to introducing this new regulatory system, we show evidence of the functions of these genes in different genomic backgrounds, and confirmed that homologous proteins from non-closely related organisms have the same function. These findings set up the basis for a new regulatory circuit of conjugative transfer of plasmids.